Analysis of the effect of Chromium concentration (Cr) in welding electrodes on Carbon diffusion (C) at weld interface of ASTM A213 T22 material using metallographic and hardness testing methods - Ruskandi, C.; Firmansyah, M.O.; Purwadi, W. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2019)
In joinning superheater pipes ASTM A213 T22 and ASTM A213 T91 by welding there is carbon diffusion from the parent metal ASTM A213 T22 to the weld seam. According to Nemoto’s research, this could occur because the Cr concentration in ASTM A213 T22 metal is lower than the Cr concentration in the electrode. Diffusion of carbon can reduce the mechanical properties of the parent metal so that it can cause the formation of type IV weld crack. This study aims to analyze the effect of Cr concentration in electrodes on the carbon diffusion on the ASTM A213 T22 parent metal interface. The metal is welded using the AWS A5.5 standard electrodes with the difference in Cr content and then followed by post weld heattreatment at a temperature of 750oC for 5 hours. Metallographic and hardness test results showed that the electrode which have a greater Cr content than the parent metal caused carbon diffusion after heattreatment. Whereas those which have a lower Cr concentration than the parent metal did not cause carbon diffusion. The result proved that the diffusion of carbon on the weld of ASTM A213 T22 metal occured on an uphill basis, namely carbon diffusion occurs from lower Cr concentration to a higher Cr concentration metals. The result of this research are in line with the research of Darken and Nemoto where carbon diffusion occurs uphill due to changes in carbon chemical potential gradients caused by differences in concentration such as Cr or Si